Moral Error Theory - Kalf, Wouter Floris (Springer International Publishing, 2018)
This book provides a novel formulation and defence of moral error theory. It also provides a novel solution to the so-called now what question; viz., the question what we should do with our moral thought and talk after moral error theory. The novel formulation of moral error theory uses pragmatic presupposition rather than conceptual entailment to argue that moral judgments carry a non-negotiable commitment to categorical moral reasons. The new answer to the now what question is pragmatic presupposition substitutionism: we should substitute our current moral judgments, which pragmatically presuppose the existence of categorical moral reasons with 'schmoral' judgments that pragmatically presuppose the existence of a specific class of prudential reasons. These are prudential reasons that, when we act on them, contribute to the satisfaction of what the author calls 'the fundamental desire'; namely, the desire to live in a world with mutually beneficial cooperation.